SEVERE CORONAVIRUS INFECTIONS IN PREGNANCY: A SYSTEMATIC REVIEW - Putri Nurfauzia, Yunike (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: A systematic literature review was undertaken to examine case reports pertaining to Middle East respiratory syndrome coronavirus (MERS-CoV), severe acute respiratory syndrome coronavirus (SARS-CoV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19, in the context of pregnancy. Objective: The objective was to provide a comprehensive overview of the clinical manifestations, disease progression, and outcomes for both pregnant individuals and their neonates. Methods: A comprehensive search was conducted on the MEDLINE and ClinicalTrials.gov databases, covering the period from their establishment up until August 3, 2023. The author incorporated articles that present case-level data about the infection of pregnant women with MERS-CoV, SARS-CoV, and SARS-CoV-2. The course of sickness, markers of severe disease, maternal health outcomes, and pregnancy outcomes were extracted from the articles that were included. Results: A total of 1,328 distinct publications were found, with 1,253 articles being removed based on the evaluation of their titles and abstracts. A comprehensive examination was conducted on a total of 75 publications, out of which 29 papers were deemed ineligible and hence eliminated from the analysis throughout the full-text review process. Out of the 46 papers that provided case-level data, eight publications presented information on 12 instances of MERS-CoV infection, seven publications discussed 17 cases of SARS-CoV infection, and 31 publications detailed 98 cases of SARS-CoV-2 infection. The clinical presentation and progression of the illness varied over a spectrum, ranging from individuals who showed no symptoms to those who experienced severe and ultimately deadly disease. This pattern was consistent with what is typically observed in the broader population of patients. The occurrence of significant morbidity and mortality in women who contract MERSCoV, SARS-CoV, or SARS-CoV-2 during pregnancy has been documented. Adverse pregnancy outcomes such as pregnancy loss, preterm delivery, and laboratory findings indicating vertical transmission have also been recorded. Conclusion: The available data on SARS-CoV, MERS-CoV, and SARS-CoV-2 infections during pregnancy are currently inadequate. However, these data can still provide valuable insights for informing early public health interventions and clinical decision-making in the context of COVID-19. It is important to note that more comprehensive and systematically gathered data are needed to further enhance our understanding of this topic.